2015
DOI: 10.1177/0308022614562790
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use amongst older adults: Knowledge and beliefs of occupational therapists working in physical health care settings

Abstract: Introduction There is little discussion in the United Kingdom occupational therapy literature surrounding the topic of older people and alcohol, despite the growing prevalence of alcohol-related health problems in older adults resulting from an ageing population and changing patterns of consumption. Occupational therapists in physical health care settings are likely to work with older people whose drinking pattern may not be alcohol dependent, but may put their physical or psychological health at risk. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In a recently completed study (Maclean et al, 2015), the authors of this study surveyed occupational therapists working in physical health care settings about their knowledge and beliefs relating to alcohol misuse amongst older adults (aged over 65 years). Knowledge of theory and assessment is essential for health care professionals working within the context of ageing and alcohol misuse (Wallace et al, 2010).…”
Section: Practice Language Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In a recently completed study (Maclean et al, 2015), the authors of this study surveyed occupational therapists working in physical health care settings about their knowledge and beliefs relating to alcohol misuse amongst older adults (aged over 65 years). Knowledge of theory and assessment is essential for health care professionals working within the context of ageing and alcohol misuse (Wallace et al, 2010).…”
Section: Practice Language Analysismentioning
confidence: 99%
“…This provided us with an opportunity to 'listen' to the language being used in these practice settings and contribute to the ongoing discussion about occupation-focused practice. Having previously identified themes (Maclean et al, 2015), we returned to our data to look in more detail at therapists' word choice. As the question did not pre-determine a specific conceptual model of practice, we were able to explore more generally the relationship between the language of practice, and the language used by current occupational therapy models.…”
Section: Practice Language Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on the theoretical perspective of person-centredness (McCormack and McCance 2017) and collective occupation (Kantartzis and Molineux 2017), this paper examines when occupational therapists in an acute hospital setting will initiate a conversation with older people (65+ years) about their drinking and how this can contribute to a wider multisystems approach. This paper builds on our prior research in the field, including a recent survey of occupational therapists in Scotland (n = 122) who indicated that they were hesitant to ask older people about their alcohol consumption when admitted to an acute hospital setting (Maclean et al 2015).…”
Section: Introductionmentioning
confidence: 99%